Sipil Muslim dalam Transisi Demokrasi di Indonesia - HERI KUSMANTO (Universitas Sumatera Utara, 2011)
Study of civil society are often conducted by political scientist. In general, a reaction to the longstanding dominance of state. Similarly, in the context of Indonesia. These studies discuss the development of the concept of civil society in Indonesia. Analytical tools used in this study is the approach of political sociology. Focused on the relation between religion and state, also talked about the political systems that shape the relationship between state and civil society. To collecting data its using the study of literature and documents and analysis was performed with the method of historical comparison. The study found that in cases in Indonesia there are Muslim intellectuals and activists who think that the concept of democracy is anti-Islamic. Conversely, there are Islamic groups who believe that even if democracy comes from the west though, it is not contrary to the ethical principles of Islam. Democracy is well used by the Islamic community. The community like this is called as civil society berteraskan Islam.Keywords: Civil society, state approach, civil muslim.